Effects of Stretch of Popliteal Fascia on Patellofemoral Pain Syndrome (Runner’s Knee) (International Journal of Physiology, 2022)
Introduction: The Patellofemoral pain syndrome (PFPS) also called Runner’s knee is a very prevalent clinicalcondition that affects about 7% to 40% of active young adults and adolescents. The popliteal fossa is coveredwith popliteal fascia that performs as a one-layer aponeurotic sheet. For hamstring muscle, popliteal fascia canbe defined as a three-layered architecture acting as a kinetic retinaculum. The aim of this project was to examineeffects of stretch of popliteal fascia on patients having patellofemoral pain syndrome.Methodology: Total of 30 patients participated, who were suffering from patellofemoral pain syndrome.The subjects were divided into 2 group and each of the group consisted of 15 participants, Group A was theExperimental Group which were given popliteal fascia stretch, and Group B was the Control Group which wasgiven popliteal fascia stretch with hamstring stretch. The improvement in pain was measured by Visual AnalogueScale (VAS) and to assess the anterior knee pain Kujala Scoring Questionnaire was measured.Result: VAS score which implicated pain was reduced in the control group as compared to experimental group.Similar findings were seen in KUJALA Scoring Questionnaire, the control group had better results in functionalityas compared to the experimental group.Conclusion: Popliteal stretch was not an effective treatment for patellofemoral pain syndrome as there wasno significant difference in Pre and Post data of pain (VAS), similar finding was founded in Kujala ScoringQuestionnaire. During the evaluation, a personalized multi modal management program is needed, which focuseson targeting patient’s functional limit as well as specific impairments.Keywords: Patellofemoral pain syndrome, popliteal fascia, hamstring muscle, popliteal fascia stretch